Seven Theorems of Joseph G. Gall. - Liu, J.L. (Experimental Cell Research, 2025)
On June 30, 2020, Professor Joseph Grafton Gall announced his retirement at 92. On August 13, 2020, Joe's former trainees and colleagues held a retirement celebration online to celebrate Joe's "Remarkable Career with Astonishing Discoveries", covering Joe's nearly 70 years of education and research. As a representative of Joe's trainees in the 2000s, I gave a speech titled "Seven Theorems of Joe". On September 12, 2024, Joe passed away peacefully, at 96. In memoriam, here I expand and update my previous speech and explain the "Seven Theorems of Joseph G. Gall", a scientists' scientist.